Comparison of the Catalytic Performance of Ni/CeO2/ZrO2 and Commercial Catalyst during Steam Reforming of Methane - Anton Purnomo; Susan Gellardo; Leonila Abella; Hirofumi Hinode; Chris Salim (ASEAN Journal of Chemical Engineering, 2008)
Catalytic performance and characterization of Ni/CeO2/ZrO2 and commercial catalyst from Indonesia were investigated in steam reforming of methane. Ni/CeO2/ZrO2 catalyst was prepared using co-impregnation of cerium nitrate and nickel nitrate onto zirconia support material. BET, SEM, EDS, XRD, TPD, TG, and ICP analyses were employed for the characterization of the catalysts. Remarkable catalytic performance of Ni/CeO2/ZrO2 catalyst at 600oC operating temperature and atmospheric pressure of about 74.9% methane conversion was obtained compared to 55.9% using the commercial catalyst. In addition, the presence of cerium in Ni/CeO2/ZrO2 was effective in improving the stability and resistance to coke formation. Less carbon formation was confirmed from the thermo-gravimetric analysis. These results showed that the prepared catalyst is promising in the industrial application which can be used at lower operation temperature for energy saving.